Optimized Analytical Solution of Platform Panel Radiative Area Dimensioning of Geostationary Communications Satellites: A Practical Approach - Murat Bulut; Nedim Sözbir (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Determiningradiative areas of geostationary satellite are one of the challenging tasks forsatellite thermal engineers at the early stage of the project. Radiative areasof geostationary communication satellite for the payload and platform panelsare determined based on worst hot case (end-of-life). After calculation of radiativeareas, it needs to be optimized according to worst hot and cold scenario at sunacquisition mode, orbit raising mode and geostationary orbit. In this study,geostationary satellite platform panel was considered. The radiator’s dimensionswere calculated and then optimized based on sun acquisition mode, orbit raisingmode and geostationary orbit. Calculated radiative areas both the north paneland the south panel was 1 m2. Radiative areas were studied at +/-10%m2. It was seen from the analytical results that the surfacetemperature of the platform panel areas were between -48.5 oC at 1.1m2 of radiative area and 37.7 oC at 0.9 m2 ofradiative area.